2017
DOI: 10.1128/mbio.00844-17
|View full text |Cite
|
Sign up to set email alerts
|

Translation Initiation from Conserved Non-AUG Codons Provides Additional Layers of Regulation and Coding Capacity

Abstract: Neurospora crassa cpc-1 and Saccharomyces cerevisiae GCN4 are homologs specifying transcription activators that drive the transcriptional response to amino acid limitation. The cpc-1 mRNA contains two upstream open reading frames (uORFs) in its >700-nucleotide (nt) 5′ leader, and its expression is controlled at the level of translation in response to amino acid starvation. We used N. crassa cell extracts and obtained data indicating that cpc-1 uORF1 and uORF2 are functionally analogous to GCN4 uORF1 and uORF4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 60 publications
3
36
0
Order By: Relevance
“…We found that multiple near-cognate start codons are used for leaky initiation in Cryptococcus: ACG for the mitochondrial isoform of LeuRS, AUU for the mitochondrial isoform of ArgRS, and the upstream CUG in eIF5. Further work will be needed to quantify the extent of near-cognate start codon usage in Cryptococcus in different growth conditions and compare it to other organisms (14, 72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that multiple near-cognate start codons are used for leaky initiation in Cryptococcus: ACG for the mitochondrial isoform of LeuRS, AUU for the mitochondrial isoform of ArgRS, and the upstream CUG in eIF5. Further work will be needed to quantify the extent of near-cognate start codon usage in Cryptococcus in different growth conditions and compare it to other organisms (14, 72).…”
Section: Discussionmentioning
confidence: 99%
“…N. crassa (strain OR74A) ribosome profiling data from ((14), GEO:GSE97717) was used to generate highly-translated genes, and ribosome profiling and RNA-seq data from ((98), GEO: GSE71032) used to estimated TE. In both cases, we estimated TPMs using the RiboViz pipeline as above, using the NC12 genome annotation downloaded from EnsembIGenomes (99).…”
Section: Methodsmentioning
confidence: 99%
“…As non-AUG initiation events are influenced by both the translation machinery and the mRNA sequence/ structure, an intriguing question is whether we can accurately predict non-AUG translation events in any given transcript. In silico tools using algorithms that are based on ribosome profiling data sets are now available to help predict true non-AUG start codons (Reuter et al 2016), and the inclusion of additional data, including secondary structure predictions (Kochetov et al 2007) and evolutionary conservation (Ivanov et al 2011(Ivanov et al , 2017, likely can improve accuracy. However, as noted in the multiple examples that were highlighted throughout this review, cellular conditions (e.g., stress) and disease mutations significantly influence start codon usage.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
“…CPC-1 is the master transcription regulator of gene expression in Neurospora in response to amino acid starvation (3,7,55,62). Like the situation of its yeast ortholog GCN4, the expression of CPC-1 is also translationally regulated by a mechanism involving uORFs (7,9).…”
Section: Discussionmentioning
confidence: 99%